The Berlin labor market since 2005: Strong employment growth yet unemployment remains high, incomes low - Karl Brenke (DIW Economic Bulletin, 2016)
Over the past ten years, the number of employed in Berlin has increased more dynamically than it has anywhere else in the country, resulting in a decrease in unemployment. But because the city's potential labor force has also experienced considerable growth, Berlin's unemployment rate remains well above the national average. Since jobs requiring intermediate qualifications have become more prevalent, this high unemployment rate is being influenced more and more by the increasing numbers of Hartz-IV recipients and lowskilled workers as well as academics. Berlin's strong employment growth has been facilitated by the fact that the productivity gains are low, even in a nationwide comparison. This is also likely one of the reasons that Berlin is still behind when it comes to wages. The weak productivity development also indicates an insufficient innovation capacity that is preventing Berlin from achieving the economic power and income levels that would befit a national capital. Now and in the future, such a transformation requires a well-qualified workforce-which is why policymakers' highest and most urgent priorities should include combating the glaring lack of apprenticeships as well as improving the quality of local schools and vocational training.
Keywords: R10; R23; R28; 330; Berlin; employment; wages; unemployment; vocational training